IMPLEMENTASI JALINAN SISTEM ANTARA GENERAL RULES DENGAN SPECIAL RULES DALAM SISTEM PEMIDANAAN SUBSTANTIF - Soponyono, Eko - (Yustisia, 2013)
AbstractImplementation of the system fabric between “general rules” with “special rules” in the substantive criminal system can not be separated from the criminal system policy will be pursued by members of the House of representatives in understanding all juridical problems are there to make a better one. Implementation of the system fabric between “general rules” with “special rules” in the substantive criminal system in Indonesia is not always ideal, because the neglect of understanding of the system of punishment in the criminal code. These conditions can be further complicated when the New penal code bill with no reforming indication intelligently addressed by the Legislature in policy formulation. Based on the above reasons, this report is organized in the hope of giving firmness to the interested student attitudes material criminal law, Law Enforcement Authorities, especially Holders Policy Formulation Phase (the Legislature).Keywords: Integrated Systems, general rules, Special rules, Sentencing System Abstrak Implementasi jalinan sistem antara “general rules” dengan “special rules” dalam sistem pemidanaan substantif   tidak dapat dipisahkan dengan kebijakan sistem pemidanaan yang akan ditempuh oleh anggota DPR dalam memahami semua permasalahan juridis yang ada untuk membuat yang lebih baik. Implementasi jalinan sistem antara “general rules” dengan “special rules” dalam sistem pemidanaan substantif di Indonesia tidak senantiasa ideal, karena terabaikannya pemahaman atas sistem pemidanaan dalam ketentuan induknya di KUHP/WvS. Kondisi demikian bisa akan lebih rumit lagi ketika RUU KUHP Baru dengan indikasi kebaharuannya tidak disikapi secara cerdas oleh Badan Legislatif dalam kebijakan formulasinya. Berdasar alasan di atas,  tulisan ini disusun dengan harapan dapat memberi ketegasan sikap bagi mahasiswa peminat hukum pidana materiil, Aparat Penegak Hukum,   terutama Pemegang Kebijakan Tahap Formulasi (Badan Legislatif ).Kata Kunci: Jalinan Sistem, Ketentuan Umum, Ketentuan Khusus, Sistem Pemidanaan